A Preliminary Study On The Polymorphism Of Hypervariable D17s5 Locus In Unimas Chinese Population - Hairul Azman, Roslan; Sim, Jessie Ann Chiew Ling; Rosmawati, Saat (UNIMAS Publisher, 2016)
Variable number of tandem repeats (VNTRs) is one of the most useful tools in the study of polymorphism and have spurred studies in many populations throughout the world. Here we report a preliminary VNTR study of the polymorphism of the hypervariable locus D17S5, in the Chinese community in UNIMAS. Samples were obtained from seventy-five unrelated Chinese individuals. The study showed the presence of six alleles ranging from 170bp to 520bp in sizes. The allele frequencies ranged from 0.02 to 0.44 with heterozygosity value of 0.32. The distributions of the D17S5 alleles in the UNIMAS Chinese population were also determined with allele 2 having the highest frequency and alleles 5 and 6 being the lowest frequencies, respectively.